Uptake of Cationic Dyes from Aqueous Solution by Biosorption onto Granular Muntingia calabura - T. Santhi; S. Manonmani; S. Ravi (E-Journal of Chemistry)
A new, low cost, locally available biomaterial was tested for its ability to remove cationic dyes from aqueous solution. A granule prepared from a mixture of leafs, fruits and twigs of Muntingia calabura had been utilized as a sorbent for uptake of three cationic dyes, methylene blue (MB), methylene red (MR) and malachite green (MG). The effects of various experimental parameters (e.g., contact time, dye concentration, adsorbent dose and pH) were investigated and optimal experimental conditions were ascertained. Above the value of initial pH 6, three dyes studied could be removed effectively. The isothermal data fitted the Langmuir and Freundlich isotherm models for all three dyes sorption. The biosorption processes followed the pseudo-first order rate kinetics. The results in this study indicated that Muntingia calabura was an attractive candidate for removing cationic dyes from the dye wastewater.